2018
DOI: 10.1002/brb3.1061
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of presymptomatic hypertension in posterior reversible encephalopathy syndrome

Abstract: ObjectiveThe effect of blood pressure (BP) on the lesion distribution of posterior reversible encephalopathy syndrome (PRES) is controversial. The aim of this study was to identify the relationship between brain lesion distribution patterns and BP.MethodsSixty‐five patients with PRES were selected from the database. Data regarding brain MRI findings, clinical symptoms, medical conditions, and BP at the presymptomatic period (24 hr before the symptom onset) and at the symptom onset were collected. The brain les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The effect of PSH on PRES severity was studied in 65 patients with PRES by Lee et al [22]. The brain lesion distribution degree, or lesion scoring point (LSP) on MRI was numerically calculated and compared with presymptomatic blood pressure.…”
Section: Pathophysiology Of Pres In Children With Malignancy or Bone Marrow Failurementioning
confidence: 99%
“…The effect of PSH on PRES severity was studied in 65 patients with PRES by Lee et al [22]. The brain lesion distribution degree, or lesion scoring point (LSP) on MRI was numerically calculated and compared with presymptomatic blood pressure.…”
Section: Pathophysiology Of Pres In Children With Malignancy or Bone Marrow Failurementioning
confidence: 99%
“…MRI findings characteristically demonstrate increased signal on T2 and FLAIR with vasogenic edema in the parieto-occipital and posterior temporal lobes, however, imaging abnormalities are not strictly confined to the posterior parieto-occipital and temporal lobes but can be seen diffusely involving the frontal lobes, basal ganglia and cerebellum [1]. One study found that patients with higher BP in presymptomatic period of PRES tended to have a larger vasogenic edematous lesions [9]. Another study published in the Mayo clinic proceedings found that the severity of edema on brain MRI did not correlate clinically with the degree of hypertension or severity of the clinical presentation [4].…”
Section: Imagingmentioning
confidence: 99%
“…[ 8 ] Patients who had relatively well-controlled hypertension in the immediate presymptomatic period were reported to have less extensive lesions by MRI. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%